The locust Schistocerca sp. (Orthoptera: Acridae) plague and its relationship with the Mega Niño of 1877-1878 in Costa Rica (UNED Research Journal, 2019)
Introduction: locust plagues have been recorded for thousands of years and were feared by many societies. Objective: to assess if the locusts that affected Costa Rica in the 19th century were related with the Mega-Niño of 1877-1878. Methods: we checked files in the Costa Rican Congress, Governance, Municipalities and Police Force. Results: clouds of locusts were reported from Guanacaste in June 1876 and in the following months the reports spread to a large part of the country, with a lesser extent in Limón. The plague affected mainly the Central American Dry Corridor (CADC) while the Mega-Niño was developing. Conclusion: meteorological data support the hypothesis that conditions generated by the Mega-Niño favored the propagation of locusts that significant damaged agriculture. The pest was combated by the army and, by the church, with prayers, until it moved to Colombia.
Keywords: Costa Rica; history; climate; El Niño; environment; agriculture; locusts.